Assessing the Impact of Community Factors on Local Community Support for Tourism: An Empirical Investigation of the China-Pakistan-Economic Corridor - Shang, Yunfeng; Pitafi, Abdul Hameed; Rashid, Rao Muhammad (Frontiers in Psychology, 2022)
This research probes the influence of the construction of the China-Pakistan Economic Corridor (CPEC) on the tourism development behavior of local residents. By applying social exchange theory (SET), this study examines the impact of the community dimension on tourism development behavior through overall attitude. In addition, this study also examines the use of social media as a moderator in the relationship between overall attitude and tourism development. A survey tool has been used to obtain data from the people of Gilgit-Baltistan. Hypotheses were examined using the structural equation method (SEM) on 417 survey responses. The findings indicated community satisfaction and an overall positive attitude to the effects of development, although a negative attitude regarding concerns about community resources. Overall, attitude has a significant impact on tourism development behavior. Additionally, the use of social media strengthens the relationship between overall attitude and behavior that favors tourism development.